Hubungan Dukungan Sosial dan Penerimaan Diri Dengan Fungsi Kognitif Pada Lansia di Tegalmulyo Nusukan Surakarta - Nanik Dewi Wahyuni; Eska Dwi Prajayanti (Yayasan Literasi Sains Indonesia, 2022)
Decreased cognitive function is a condition characterized by decreased memory and the ability to think and speak. In the elderly who experience this if not handled properly, it can cause problems such as decreased concentration and impaired perception. Data from WHO as many as 7.69% of the elderly experienced cognitive decline. The results of a preliminary study of the elderly in Nusukan Village are at high risk of experiencing cognitive decline due to low education.The decreased cognitive function causes disruption of self-acceptance in the elderly which will lead to decreased social support for the elderly. The purpose of this study was to determine whether there was a relationship between social support and self-acceptance on cognitive function in the elderly in Tegalmulyo Village, Nusukan Village. This type of research is quantitative. A simple random sampling of as many as 57 respondents. Analysis of the data used in univariate and bivariate analysis with test spearman rank. The results showed that there was a relationship between self-acceptance and cognitive function of the elderly in Tegalmulyo Nusukan (ρ value=0.000 <0.05) and there is a relationship between social support and cognitive function of the elderly in Tegalmulyo Nusukan (ρ value=0.000<0.05). This study concludes that there is a relationship between self-acceptance and social support with the cognitive function of the elderly in Tegalmulyo Nusukan.